Influence of sealer and supplementary approach on filling material removal during endodontic retreatment - Jáder Camilo PINTO; Fernanda Ferrari Esteves TORRES; Airton Oliveira SANTOS-JUNIOR; Karina Ines Medina Carita TAVARES; Juliane Maria GUERREIRO-TANOMARU; Mário TANOMARU-FILHO (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract Both root canal sealer-based and supplementary protocols may influence removal of filling material during endodontic retreatment. Mesial root canals of extracted mandibular molars were prepared using HyFlex EDM 25/.08, and filled with a calcium silicate sealer (Bio-C Sealer), or an epoxy resin (AH Plus), using the single cone technique (n = 12). Retreatment was performed using ProDesign Logic (PDL) RT and PDL 35/.05. The specimens were randomly divided into two experimental groups (n = 12), and the sealers were distributed similarly. A supplementary protocol was performed with PDL 50/.01 or XP-endo Finisher. Root canal transportation and volume, in addition to the remaining filling material percentage were evaluated using high-resolution (5 µm voxel size) micro-CT. Statistical analysis was performed using t-tests (α = 0.05). Root canals filled with AH Plus presented high residual filling material (p < 0.05). Both protocols decreased residual volume of filling material in the apical third (p < 0.05). PDL 50/.01 increased the apical root canal volume (p < 0.05). No difference was observed between the systems regarding canal transportation (p > 0.05). In conclusion, AH Plus is more difficult to remove from the apical third than Bio-C Sealer. PDL 50/.01 and XP-endo Finisher enabled greater removal of filling materials in the apical third, in the retreatment of curved root canals, without promoting apical transport.